2020
DOI: 10.3390/su12208403
|View full text |Cite
|
Sign up to set email alerts
|

Experience and Acceptance of Autonomous Shuttles in the Brussels Capital Region

Manon Feys,
Evy Rombaut,
Lieselot Vanhaverbeke

Abstract: Current technological developments allow the testing of shared autonomous electric vehicles in real-life conditions. Consequently, we can evaluate how users react and if these developments might lead to more sustainable transport behaviour in the future. The purpose of this study was to capture public opinion regarding autonomous vehicles in terms of user experience and intended future use. Autonomous shuttles were operated in the Brussels Capital Region in a mixed traffic situation, allowing interaction with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 32 publications
7
20
0
Order By: Relevance
“…Beginning in 2040, AVs will become more affordable; by 2045, it is predicted that AVs will account for 50% of all new vehicle sales [17]. Regarding public acceptance of AVs, studies (e.g., [18][19][20]) that focused on user attitudes after pilot project experiences revealed that there are positive intentions towards the technology, despite the fact that lower operation speed, inaccessibility to mobility-impaired individuals, and interaction of AVs with pedestrians and cyclists remains the concerns for their large-scale deployment.…”
Section: Introductionmentioning
confidence: 99%
“…Beginning in 2040, AVs will become more affordable; by 2045, it is predicted that AVs will account for 50% of all new vehicle sales [17]. Regarding public acceptance of AVs, studies (e.g., [18][19][20]) that focused on user attitudes after pilot project experiences revealed that there are positive intentions towards the technology, despite the fact that lower operation speed, inaccessibility to mobility-impaired individuals, and interaction of AVs with pedestrians and cyclists remains the concerns for their large-scale deployment.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the absence of staff was not an issue for frequent users of autonomous shuttle services in Trikala, Greece (Portouli et al, 2017). Vehicle operational safety and technical issues (e.g., traffic crashes caused by technical errors, confusion when an unprecedented situation occurs) were the other top concerns voiced by the respondents (Chng and Cheah, 2020;Feys et al, 2020;Dong et al, 2019;Lopez-lambas and Alonso, 2019;Roche-Cerasi, 2019;Bansal et al, 2016). However, in some studies, respondents agreed that there was less risk of a traffic crash for autonomous transit than for conventional transit (Portouli et al, 2017;Salonen, 2018).…”
Section: Public Perceptionmentioning
confidence: 99%
“…However, in some studies, respondents agreed that there was less risk of a traffic crash for autonomous transit than for conventional transit (Portouli et al, 2017;Salonen, 2018). Among others, respondents expressed concerns about potential hazards ensuing from AVs sharing the roadway with pedestrians (Battistini et al, 2020) and conventional vehicles (Bansal et al, 2016;Battistini et al, 2020), particularly in complex urban situations (Feys et al, 2020), legal liabilities in case of a traffic crash (Chng and Cheah, 2020), increased investment costs for vehicles and infrastructural improvement (Lopez-Lambas and Alonso, 2019), potential reduction in funding for traditional transit (Battistini et al, 2020), job loss due to automation (Tussyadiah et al, 2017), and affordability of the service (Bansal et al, 2016).…”
Section: Public Perceptionmentioning
confidence: 99%
See 2 more Smart Citations